مستوى التعلم المنظم ذاتيا لدى تلاميذ السنة رابعة متوسط - الأسود، صباح (جامعة الوادي university of Eloued, 2021)
الملخص: تهدف الدراسة الحالية إلي معرفة مستوى التعلم المنظم ذاتيا لدى تلاميذ السنة الرابعة متوسط بمتوسطة عقاب سالم (حاسي خليفة) وما مدى استخدام الاستراتيجيات التعلم المنظم ذاتيا بأبعاده الثلاث المعرفي وما وراء المعرفي وإدارة المصادر . • وقد تحددت الدراسة بالمنهج الوصفي الاستكشافي وعلى عتبة مقدرا ب80 تلميذ وتلميذة من مستوي الرابعة متوسط . لسنة الدراسية 2020/2021 م والتي تم اختبارها بالطرقة القصدية . وقد اعتمدت الدراسة على أداة في جمع البيانات والمتمثلة في مقياس إستراتيجيات التعلم المنظم ذاتيا فجاءت تساؤلات الدراسة على النحو التالي : التساؤل العام : ما مستوى التعلم المنظم ذاتيا لدى تلاميذ الرابعة متوسط ؟ التساؤلات الفرعية : 1. ما مستوى التعلم المنظم ذاتيا في البعد المعرفي لدى تلاميذ السنة الرابعة المتوسطة ؟ 2. ما مستوى التعلم المنظم ذاتيا في البعد ما وراء المعرفي لدى تلاميذ السنة الرابعة متوسط ؟ 3. ما مستوى التعلم المنظم ذاتيا في بعد إدارة المصادر لدى تلاميذ السنة الرابعة متوسط.؟ • وباستخدام الأسلوب الإحصائي المتمثل في المتوسط الحسابي والانحراف المعياري والنسبة المئوية عن طريق تطبيق البرنامج الإحصائي spss توصلنا النتائج التالية : يوجد اختلاف بين التلاميذ في استخدام استراتيجيات التعلم المنظم ذاتيا حسب درجة (منخفضة -متوسطة – مرتفعة ). 1. تستخدم الاستراتيجيات المعرفية بدرجة مرتفعة بنسبة مئوية مقدرة ب43 % 2. تستخدم الاستراتيجيات ما وراء المعرفية بدرجة مرتفعة بنسبة مئوية مقدرة ب48%. 3. تستخدم الاستراتيجيات إدارة المصادر بدرجة مرتفعة بنسبة مئوية مقدرة ب 51% وفي الأخير تم تفسير هذه الدراسة في ضوء بعض الدراسات السابقة والتراث النظري وختمت الدراسة ببعض التوصيات التي من شأنها أن تفتح الباب لبحوث جديدة. Abstract: Summary of The Research " The" The current study aims to know the level of self-orgamised learning among fourth –year students ,in Agab Salen Middle School in El-Hamaissa (Hassi-khalifa). And the level to which self-organized learning strategies are used in its three dimensions ;the cognitive dimension ,the meta –cognitive dimension and the resources management. The study was determined by the exploratory descriptive approach on a sample of 80 students of fourth grade middle school for 2020/2021 school year in which was chosen in purpose. This study basedon a way-to gather the results –which is represented in the s-cale of self –regulated learning strategies .So the claims of this study was posed as the following: • The general claim: • What is the level of self-organized learning among fourth grade Middle school students ? • The sub - claims: 1- What is the level of self-regulated learning in the cognitive dimension of fourth year middle school students? 2- What is the level of self –regulated learning in the meta-cognitive dimension of fourth year middle school students ? 3- What is the level of self-regulated learnimg in the resources management of fourth year middle school grade? Within the use of the Arthmetic mean , standard deviation md the percentages , we had got the following results: There is a difference between the students in using the self-regulated learning strategies according to the degree (low, medium ,high). • The Cognitive strategies are used to a high degree ,with an estimated percentage of 43%. • The meta-cognitive strategies are used to a high degree ,with an estimated percentage of 48%. • The resources management ; strategies are used to a high degree with an estimated percentage of 51%. At last ,this study was interpreted under some previous studies and a theoretical heritage .And it Was concluded with some recommendations which can open new doors for new researches.
دراسة ميدانية متوسطة عقاب سالم الهمايسة حاسي خليفة
مذكرة ماستر علم الاجتماع تخصص تربية خاصة
Keywords: التعلم المنظم ذاتيا، مرحلة التعليم المتوسط; Apprentissage auto-organisé, niveau collège; Self-organized learning, middle school stage